Presidios of Spanish West Florida - Bense, Judith Ann (Book collections on Project MUSE., 2022)
Bense details a history fraught with catastrophe-hurricanes, war against France and England, and treaties that forced the Spanish base in West Florida to be uprooted and rebuilt four times. Examining each presidio, including associated military outposts, shipwrecks, and refugee mission villages of the Apalachee and Yamasee Indians, this book provides four discrete, sequential windows into the Spanish presence in the region. Bense compares the population to that of Presidio San Agustin, established 133 years later, revealing very different communities, people, and local customs. Interwoven with these historical findings is an account of how the general public has participated in investigations in the region, providing readers with an understanding of eighteenth-century West Florida and the development of public archaeology in the state from the person who initiated and directed much of the research. A volume in the Florida Museum of Natural History: Ripley P. Bullen Series"--